x ^{2} + 11x + 28 factorize this equation step by step​

Question

x ^{2}  + 11x + 28
factorize this equation step by step​

in progress 0
Kylie 1 month 2021-09-10T17:41:12+00:00 2 Answers 0 views 0

Answers ( )

    0
    2021-09-10T17:42:19+00:00

    Answer:

    {\sf{\underline{\red{Answer:-}}}}x^2 = 11x - 28 , in this two solutions can be found, x = 7 and x = 4Method:First, by rearranging the equation by subtracting what is to the right of the equal sign from both sides of the equarion:x^2 - 11*x - (-28) = 0STEP BY STEP SOLUTION:➜Factoring x^2 - 11x + 28The first you see is, x^2 it's coefficient is 1.The middle term is, - 11x it's coefficient is - 11.The last term, "the constant", is + 28.→Step-1: Multiply the coefficient of the first term by the constant, that is, 1 × 28 = 28→Step-2: Find two factors of 28 whose sum equal the coefficient number of the middle term, which should - 11.- 28 + -1 = -29- 14 + -2 = -16- 7 + - 4 = -11 That's it!!→Step-3: Rewrite the polynomial splitting the middle term using the two factors found in step 2 above, - 7 and - 4.x^2 - 7x - 4x - 28→Step-4: Add up the first 2 terms, pulling out like factors:x × (x - 7)Add up the last two terms, pulling out common factors:4 × (x - 7)→Step-5: Add up the four terms of step 4:(x - 4) × (x - 7)[Tex]\boxed{\red{which/:is/:desired/:as/:factorisation}}

    0
    2021-09-10T17:42:54+00:00

    \huge\mathfrak\blue{Answer:-}

     <font color = white >

    x^2 = 11x – 28 , in this two solutions can be found, x = 7 and x = 4

    Method:

    First, by rearranging the equation by subtracting what is to the right of the equal sign from both sides of the equarion:

    x^2 – 11*x – (-28) = 0

    STEP BY STEP SOLUTION:

    Factoring x^2 – 11x + 28

    The first you see is, x^2 it’s coefficient is 1.

    The middle term is, – 11x it’s coefficient is – 11.

    The last term, “the constant”, is + 28.

    Step-1: Multiply the coefficient of the first term by the constant, that is,

    1 \times 28 = 28

    Step-2: Find two factors of 28 whose sum equal the coefficient number of the middle term, which should – 11.

     - 28 + 1 =  ( - 29) \\  - 14 + ( - 2) = ( - 16) \\  - 7 + ( - 4) = ( - 11)

    That’s it!!

    Step-3: Rewrite the polynomial splitting the middle term using the two factors found in step 2 above, – 7 and – 4.

     {x}^{2}  - 7x - 4x - 28

    Step-4: Add up the first 2 terms, pulling out like factors:

    x \times (x - 7)

    Add up the last two terms, pulling out common factors:

    4 \times (x - 7)

    Step-5: Add up the four terms of step 4:

    (x - 4) \times (x - 7)

    _____♡

    Hope it helps you ❤️

     <html> <head> <meta name="viewport" content="width=device-width, initial-scale=1"> <style> Body{ background-color: black; font-family: cursive; } .glow{ font-size: 80px; color: #fff; text-align: center; -webkit-animation: glow 1s ease-in-out infinite alternate; -moz-animation: glow 1s ease-in-out infinite alternate; animation: glow 1s ease-in-out infinite alternate; } @-webkit-keyframes glow{ from{ text-shadow: 0 0 10px #fff, 0 0 20px #fff, 0 0 30px #e60073, 0 0 40px #e60073, 0 0 50px #e60073, 0 0 60px #e60073, 0 0 70px #e60073; } } </style> </head> <body> <h1 class="glow">️</h1> </body> </html>

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )